-(3с-2d)-(3d+2c)+(-4c+2d)=-3с+2d-3d-2c-4c+2d=d-9c
-3c+2d-3d-2c-4c+2d
Пошаговое объяснение:
-(3с-2d)-(3d+2c)+(-4c+2d) [условие]
Раскрываем скобки:
-3c + 2d - 3d - 2c - 4c + 2d [тут мы раскрыли скобки]
Приводим подобные члены:
-9c+d [тут мы пришли к решению]
-(3с-2d)-(3d+2c)+(-4c+2d)=-3с+2d-3d-2c-4c+2d=d-9c
-3c+2d-3d-2c-4c+2d
Пошаговое объяснение:
-(3с-2d)-(3d+2c)+(-4c+2d) [условие]
Раскрываем скобки:
-3c + 2d - 3d - 2c - 4c + 2d [тут мы раскрыли скобки]
Приводим подобные члены:
-9c+d [тут мы пришли к решению]